Planets to cosmology : essential science in the final years of the Hubble Space Telescope : proceedings of the Space Telescope Science Institute Symposium, held in Baltimore, Maryland, May 3-6, 2004 - Space Telescope Science Institute (U.S.). Symposium (2004 : Baltimore, Md.); Livio, Mario, 1945-; Casertano, Stefano (Cambridge, UK : Cambridge Univ Pr., 2006)
26